Duodenal Ulcer and Recurrent Dyspepsia. Issue 5719 (15th August 1970) - Hodgkin, G. K. H.; Freedman, R.; Fuller, I.; Whewell, J.
Abstract : A survey of recurrent indigestion in four general practices (19, 619 patients) showed a wide range of dyspeptic complaints. Of these 82 (4·2 per 1, 000) already had a proved ulcer and 144 (7·3 per 1, 000) had symptoms suggesting a duodenal ulcer and had either not been investigated or had previously had a normal barium meal. A duodenal ulcer was found radiologically in half the men (46 out of 95) but in only 16% of the women (8 out of 49). In 11 (25%) of the 46 men shown to have an ulcer a barium meal had been previously reported as normal. Evidence is put forward that ulcer symptoms in the large residue of patients with a normal barium meal (38 men, 29 women) were produced by a primary duodenal condition (duodenitis) of which ulcer was one complication.